Selection of Reference Genes for Real-time Quantitative PCR Normalization in the Process of Gaeumannomyces graminis var. tritici Infecting Wheat - Xie, Li-hua (Plant Pathol J, 2019)
Gaeumannomyces graminis var. tritici is a soil borne pathogenic fungus associated with wheat roots. The accurate quantification of gene expression during the process of infection might be helpful to understand the pathogenic molecular mechanism. However, this method requires suitable reference genes for transcript normalization. In this study, nine candidate reference genes were chosen, and the specificity of the primers were investigated by melting curves of PCR products. The expression stability of these nine candidates was determined with three programs-geNorm, Norm Finder, and Best Keeper. TUBβ was identified as the most stable reference gene. Furthermore, the exopolygalacturonase gene (ExoPG) was selected to verify the reliability of TUBβ expression. The expression profile of ExoPG assessed using TUBβ agreed with the results of digital gene expression analysis by RNA-Seq. This study is the first systematic exploration of the optimal reference genes in the infection process of Gaeumannomyces graminis var. tritici.